Sporadic Hemiplegic Migraine with ATP1A2 and Prothrombin Gene Mutations. (11th December 2013) - Aceves, Jose; Mungall, Diana; Kirmani, Batool F.
Abstract : Background . Hemiplegic migraine is a rare type of migraine that may present in children and adolescents. Both familial and sporadic hemiplegic migraines have similar prevalence and clinical characteristics. Patient . We report an adolescent with sporadic hemiplegic migraine who previously had a similar attack in the past and who was initially evaluated for a possible acute ischemic event. Results . Magnetic resonance angiography showed dilatation of the left middle cerebral artery that resolved in a follow-up study. She was also found to have a ATP1A2 (c.2273 G>C) mutation and a heterozygous prothrombin mutation. Conclusions . We suggest that patients with sporadic hemiplegic migraine be tested for both ATP1A2 mutations which in some cases may be pathogenic, and prothrombin mutations which increase the stroke risk for this patient population.